1998
DOI: 10.1016/s0032-3861(97)00420-5
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of melting and crystallization in poly(ethylene oxide) by atomic force microscopy

Abstract: The processes of melting and crystallization of poly(ethylene oxide) are followed in real time at elevated temperature by atomic force microscopy using a simple hot stage apparatus. Hedritic development at a temperature of 5~7°C is monitored, including the process of lamellar splaying to yield a spherical morphology. Crystal growth kinetics are measured by monitoring the growth of individual lamellae and found to agree with those obtained by conventional optical microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 18 publications
1
53
1
Order By: Relevance
“…Several research groups have studied the spherulite morphology and their growth using in situ AFM and TEM for poly(ε-caprolactone) (PCL), 25,26 poly(triflouroethylene) (PF 3 E), 27 poly(bisphenol A-co-octane) (PBAC8), 29 poly(ethylene terephthalate) (PET), 30,31 poly(ethylene oxide) (PEO), [32][33][34] isotactic polystyrene (i-PS), 35 and polyethylene (PE). 36 All of these studies show that the polymer crystals grow from a central nucleus.…”
Section: Spherulitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several research groups have studied the spherulite morphology and their growth using in situ AFM and TEM for poly(ε-caprolactone) (PCL), 25,26 poly(triflouroethylene) (PF 3 E), 27 poly(bisphenol A-co-octane) (PBAC8), 29 poly(ethylene terephthalate) (PET), 30,31 poly(ethylene oxide) (PEO), [32][33][34] isotactic polystyrene (i-PS), 35 and polyethylene (PE). 36 All of these studies show that the polymer crystals grow from a central nucleus.…”
Section: Spherulitesmentioning
confidence: 99%
“…AFM is equipped to study crystallization in situ over a large temperature range. 25 Using the tapping mode, one can visualize the crystal morphology as well as determine the crystal thickness, which are both a function of ∆Τ. The hot stage attachment allows one to change the temperature of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning probe microscopy offers the opportunity to follow crystal growth at a surface in real-time, with nanometer resolution, and hence to quantify the kinetics by direct observation at length scales that are close to those of the fundamental crystallizing unit, and to the size scale of the polymer chain (92,(145)(146)(147)(148)(149)(150)(151)(152). Several groups (145)(146)(147)149) have reported that lamella crystallization from the melt, at least where several lamellae are growing adjacently, does not occur at a constant temperature-controlled rate. Instead, growth rates are sporadic over length scales of several tens of nanometers, with lamellae or parts of lamellae spurting forwards briefly, then slowing down and being overtaken by their neighbors (146).…”
Section: New Approaches To Crystallization Kineticsmentioning
confidence: 99%
“…Some recent research has been focused on observing the crystal growth in situ and in real space by scanning force microscopy (SFM) [2][3][4][5][6][7][8][9][10]. These experiments gave new insights on individual local events during crystallization.…”
Section: Introductionmentioning
confidence: 99%